Pengaruh Pengalaman Praktik Kependidikan Terhadap Minat Dan Efikasi Diri Mahasiswa Menjadi Guru SMK Otomotif: Inggris, Indonesia - Agil Aditya Febriansyah; Tafakur Tafakur (Journal of Automotive Technology and Education, 2025)
Abstract This study aims to: (1) Analyze the impact of Educational Practice Experience (PK) on the interest in becoming a teacher at an Automotive Vocational High School for students of the Automotive Engineering Education Study Program, class of 2021 at the Faculty of Engineering, Yogyakarta State University. (2) Analyze the impact of Educational Practice Experience (PK) on self-efficacy in becoming an Automotive Vocational High School teacher for students of the Automotive Engineering Education Study Program, class of 2021 at the Faculty of Engineering, Yogyakarta State University. This study applies a quantitative approach. The population studied consisted of all students of the class of 2021 in the Automotive Engineering Education Study Program who had implemented the PK program in 2024, with a total of 105 individuals. In this study, samples were taken using the Slovin formula with a tolerance for error of 5%, resulting in 83 respondents. The validity test was carried out through Expert Judgment, while the reliability was tested with Alpha Cronbach. The analysis assumption test includes normality, linearity, and heteroscedasticity tests. Data analysis was carried out using the simple regression method. The research findings show: (1) There is a positive and significant influence of educational practice experience on students' interest in becoming automotive vocational school teachers, with a t-value of 6.347, a regression coefficient of 0.612, a significance value of 0.000, and a determination coefficient (R²) of 0.332 or 33.2%, while the remaining 66.8% is influenced by other factors not examined in this study. (2) There is a positive and significant influence of educational practice experience on students' self-efficacy in becoming automotive vocational school teachers, with a t-value of 11.351, a regression coefficient of 0.866, a significance value of 0.000, and a determination coefficient (R²) of 0.614 or 61.4%, while the remaining 38.6% is influenced by other factors not analyzed in this study.   Abstrak Studi ini memiliki tujuan untuk: (1) Menganalisis dampak Pengalaman Praktik Kependidikan (PK) terhadap ketertarikan untuk menjadi guru di SMK Otomotif. (2) Menganalisis dampak Pengalaman Praktik Kependidikan (PK) terhadap efikasi diri dalam menjadi guru SMK Otomotif. Penelitian ini mengaplikasikan pendekatan kuantitatif. Populasi yang diteliti terdiri dari seluruh mahasiswa angkatan 2021 dalam Program Studi Pendidikan Teknik Otomotif yang telah melaksanakan program PK di tahun 2024, dengan total sebanyak 105 individu. Dalam penelitian ini menggunakan sampel sebanyak 83 responden. Uji validitas dilakukan melalui Expert Judgement, sementara reliabilitas diuji dengan Alpha Cronbach. Uji asumsi analisis mencakup uji normalitas, linearitas, dan heteroskedastisitas. Analisis data dilakukan dengan metode regresi sederhana. Temuan penelitian menunjukkan: (1) Ada pengaruh positif dan signifikan dari pengalaman praktik kependidikan terhadap ketertarikan mahasiswa untuk menjadi guru SMK otomotif, dengan nilai t-hitung sebesar 6,347, koefisien regresi 0,612, nilai signifikansi 0,000, dan koefisien determinasi (R²) sebesar 0,332 atau 33,2%, sementara sisanya 66,8% dipengaruhi oleh faktor lain yang tidak diteliti dalam penelitian ini. (2) Ada pengaruh positif dan signifikan dari pengalaman praktik kependidikan terhadap efikasi diri mahasiswa menjadi guru SMK otomotif, dengan nilai t-hitung 11,351, koefisien regresi 0,866, nilai signifikansi 0,000, dan koefisien determinasi (R²) sebesar 0,614 atau 61,4%, sedangkan sisanya 38,6% dipengaruhi oleh faktor lain yang tidak dianalisis dalam penelitian ini.